Gender and Climate Change Vulnerability Hotspot Mapping in Agriculture, Water and Energy Sector for Decision Support in Uganda - African Group of Negociators Experts Support; Bill and Melinda Gates Fundation (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
The granular gender and climate change vulnerability hotspot mapping for decision support study in Uganda reveals sub-national level gendered climate vulnerabilities that require policy intervention to build community resilience to the impacts of climate change in the three sectors of agriculture, water and energy.